Proceedings: The international conference on integrated fisheries monitoring, Syney, Australia, 1 - 5 February 1999 - FAO (FAO, 1999)
The book adresses the chalenges and opportunities of fisheries monitoring that are common to many fisheries. It discusses around five main themes: Rationale for monitoring programmes - conceptual and legal frameworks; Perspectives on monitoring from key stakeholders; Designing, executing and analysing monitoring programmes; Key components and issues for monitoring programmes; and Integrated monitoring.